Peran Green Marketing Terhadap Minat Beli Melalui Kepercayaan Merek (Studi Pada Produk Love Beauty and Planet) - Alda Oktitania Askaria; Mohammad Arief (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
Environmental pollution continues to increase every year and the beauty industry is one of the environmental pollution that we need to face right now. This research was conducted to determine the effect of green marketing on purchase intention through brand trust of environmentally friendly products.The research approach used is quantitative with an explanatory method. The population in this study are respondents who know about Love Beauty and Planet products. The results showed that there was a positive influence of green marketing on trust of environmentally friendly products, there was a positive influence of green marketing on purchase intention, there was a positive influence of trust in environmentally friendly product on purchase intention, and there was an indirect effect of green marketing on purchase intention through trust environmentally friendly product. In this study, brand trust for environmentally friendly products fully mediates the effect of green marketing on purchase intention.